PENDAMPINGAN PEMBUATAN AUTOMATIC WASTAFEL UNTUK PENCEGAHAN PENULARAN COVID-19 DI SEKOLAH MENENGAH KEJURUAN - Puspitasari, Niken Sylvia; Musthafa, Aziz; Wahid, Abdul (UNIVERSITAS PGRI MADIUN, 2022)
Abstract Community empowerment activities at SMK PGRI 1 Ponorogo is focused on providing assistance in making automatic sinks. The purpose of this community empowerment is as downstream research results of the author on automatic sink technology as one of the tools to prevent the transmission of covid-19. This method of community empowerment is mentoring teachers and student of SMK PGRI 1 Ponorogo in making automatic sinks. The form of activity carried out is a seminar by the implementing team to partners on the manufacture of this technology. Through the transfer of knowledge in community empowerment activities, it is expected that partners can implement in the manufacture and development of tools independently. The results of this community empowerment can increase the knowledge of partners related to the manufacture of automatic sinks as one of the efforts to overcome the transmission of covid-19 in schools.Abstrak Kegiatan Pengabdian masyarakat di SMK PGRI 1 Ponorogo ini berfokus untuk memberikan pendampingan pembuatan automatic wastafel. Tujuan pengabdian masyarakat ini adalah sebagai hilirisasi hasil riset penulis tentang teknologi automatic wastafel sebagai salah satu alat untuk mencegah penularan covid-19. Metode pengabdian masyarakat ini adalah pendampingan kepada guru dan siswa SMK PGRI 1 Ponorogo dalam membuat automatic wastafel. Bentuk kegiatan yang dilakukan adalah seminar oleh tim pelaksana kepada mitra mengenai pembuatan teknologi ini. Melalui transfer ilmu dalam kegiatan pengabdian masyarakat ini diharapkan mitra dapat mengimplementasikan dalam pembuatan dan pengembangan alat secara mandiri. Hasil pengabdian masyarakat ini dapat meningkatnya pengetahuan mitra terkait pembuatan automatic wastafel sebagai salah satu upaya mengatasi penularan covid-19 di sekolah